Testimonials from CLIFF-GRADS scholarship awardees from round 2 - Ruíz, Deysi; Pérez, Gabriela; Turcato, Maria Carolina Scorcione; Alvarado, Victor (Global Research Alliance on Agricultural Greenhouse Gases (GRA) & CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS), 2020)
Testimonials and feedback from four CLIFF-GRADS Round 2 (2019) students. Their research focused on livestock system emmissons in Argentina.